THE ROLE OF THE RUSSIAN LANGUAGE IN SOCIETY (Web of Teachers: Inderscience Research, 2024)
This article delves into the multifaceted role of the Russian language in contemporary society, exploring its historical significance, cultural implications, and contemporary relevance. Through a comprehensive literature analysis, this study aims to shed light on the various dimensions of the Russian language, examining its impact on identity, communication, and international relations. By employing a systematic approach, this research provides valuable insights into the language's dynamic role in shaping societal dynamics.